Internal And External Risks Threatening The Stability Of Small Businesses: A Systematic Analysis - Umarov, Azizjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article studies internal and external risks that threaten the stable operation of small businesses based on a systematic approach. Internal risks include factors such as management shortcomings, lack of financial resources, and low employee qualifications, while external risks are associated with factors such as global economic instability, changes in tax policy, and sharp fluctuations in market demand. The article discusses the interaction of these risks, the degree of their impact on the stability of small businesses, and recommendations for their reduction. Through systematic analysis, approaches based on early identification of risks and strategic management are developed.